“Efficacy of IGRA in the Diagnosis of Tuberculosis and its Correlation with Fluorescence Microscopy and Chest X-Ray in a Tertiary Care Setting in Sikkim” - Choudhary, Preety; Singh, Dr. T. S. K; Adhikari, Dr. Luna; Nandy, Dr. Parvati (International Journal of Innovative Research in Medical Science, 2017)
Background: Studies have shown Interferon gamma release assay as an aid in diagnosing Mycobacterium tuberculosis infection, including latent tuberculosis infection. This study intended to evaluate the efficacy of IGRA in case detection of pulmonary tuberculosis and correlation with fluorescence microscopy and chest x-ray findings. Methods: Clinically suspected patients (N=300) of pulmonary tuberculosis with chest x-ray findings were screened by fluorescence microscopy and IGRA. Each patient was subjected to IGRA, to diagnose active as well as latent infection. Results: Overall 300 patients were enrolled. A total of 89% correlation was observed between IGRA and fluorescence microscopy with the two-sided P-value=0.0022, considered very significant. 100% correlation was observed between chest x-ray results and IGRA. However, 63% correlation was observed between fluorescence microscopy and Chest x-ray findings. IGRA was found to be 100% sensitive and 99.09% specific and an efficacy of 100%. However, fluorescence microscopy showed a sensitivity of 62.5%, specificity of 100%, with an efficacy of 90%. Conclusion: IGRA is a reliable tool for diagnosis as compared to fluorescence microscopy. It is more sensitive, specific and accurate than fluorescence microscopy. It can be a better diagnostic tool in case detection among children.